Indonesian Aviation Act 1/2009: An Examination and the Quest for Reform in Certain Issues - Adhy Riadhy Arafah; Rosa Ristawati; Kautsar Ismail; Gerlyana Shafa Putri Hardriani (Communications)
Indonesian Aviation Act 1/2009, which has been adopted for more than 14 years ago, was made to accommodate the ICAO's Universal Safety Oversight Audit Programme (USOAP) findings in 2007, which highlighted the need for legislative changes to reduce air transport accidents in Indonesia. The Act regulates two aspects of aviation activity, covering the public and private. The public sector regulates aircraft activities in Indonesia's airspace, certain issues are missed owing to (the) controversy over its legal terminology. In the private sector, the jurisdiction issue and applicability of the Act have consequently regarding the applicability of the Montreal Convention 1999 was ratified by Indonesia in 2016. In this paper were examined some provisions in the Act by normative juridical and comparative approaches, emphasizing the urgent need for legal reform. It is ultimately recommended to amending the Act to align it with current conditions.